Canine distemper virus isolated from a monkey efficiently replicates on Vero cells expressing non-human primate SLAM receptors but not human SLAM receptor. Issue 1 (December 2016) - Feng, Na; Liu, Yuxiu; Wang, Jianzhong; Xu, Weiwei; Li, Tiansong; Wang, Tiecheng; Wang, Lei; Yu, Yicong; Wang, Hualei; Zhao, Yongkun; Yang, Songtao; Gao, Yuwei; et al.
Abstract Background In 2008, an outbreak of canine distemper virus (CDV) infection in monkeys was reported in China. We isolated CDV strain (subsequently named Monkey-BJ01-DV) from lung tissue obtained from a rhesus monkey that died in this outbreak. We evaluated the ability of this virus on Vero cells expressing SLAM receptors from dog, monkey and human origin, and analyzed the H gene of Monkey-BJ01-DV with other strains. Results The Monkey-BJ01-DV isolate replicated to the highest titer on Vero cells expressing dog-origin SLAM (105.2±0.2 TCID50 /ml) and monkey-origin SLAM (105.4±0.1 TCID50 /ml), but achieved markedly lower titers on human-origin SLAM cells (103.3±0.3 TCID50 /ml). Phylogenetic analysis of the full-length H gene showed that Monkey-BJ01-DV was highly related to other CDV strains obtained during recent CDV epidemics among species of the Canidae family in China, and these Monkey strains CDV (Monkey-BJ01-DV, CYN07-dV, Monkey-KM-01) possessed a number of amino acid specific substitutions (E276V, Q392R, D435Y and I542F) compared to the H protein of CDV epidemic in other animals at the same period. Conclusions Our results suggested that the monkey origin-CDV-H protein could possess specific substitutions to adapt to the new host. Monkey-BJ01-DV can efficiently use monkey- and dog-origin SLAM to infect and replicate in host cells, but further adaptation may be required for efficient replication in host cells expressing the human SLAM receptor.